The use of upper limb prosthesis optimizes long jump approach kinematics: a case study of an elite T47 athlete - Theodorou, A.; Tsiokos, N.; Papadopoulou, E.; Panoutsakopoulos, V.; Kotzamanidou, M. C.; Exell, T. (ISBS Proceedings Archive (Michigan), 2020)
This study aimed to investigate approach run kinematics using an upper limb prosthesis. A European T47 long- and triple- jump champion with right upper-limb congenital deficiency was analyzed in simulated approach run-ups wearing prosthesis (PW) or not (NP). Two attempts in each condition were recorded (300 fps). Step characteristics and kinematic parameters were extracted for the deficient (DLS) and intact (HLS) sides with a 2D-DLT analysis during the early (EA) and late (LA) approach. Results revealed systematic asymmetry for step frequency and length in NP, with the latter reduced in PW. Horizontal velocity in both EA and LA was larger by 0.3 m/s in PW than NP. These results suggest that asymmetry of NP reduces approach run performance compared to PW.